2021
DOI: 10.1007/s42399-021-00790-x
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection or Reactivation of Coronavirus-19 in Patients with Hematologic Malignancies: Case Report Series

Abstract: Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been relentless. We are into the 10th month of the pandemic, and we are still getting surprised every day. Although neutralizing antibodies are generated in response to coronavirus disease-19 (COVID-19), these antibodies do not appear to confer lifelong immunity, as lately there have been reports from various parts of the world of reinfection with the virus, starting from Hong Kong, Belgium, and the USA. The Indian Council of Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Likewise, 10 studies were identified via citation searching. These 10 were sought for retrieval and then assessed for eligibility [ 12 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ,…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, 10 studies were identified via citation searching. These 10 were sought for retrieval and then assessed for eligibility [ 12 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ,…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility that could allow the reinfection of a patient is the reactivation of dormant virus which is commonly seen in immunosuppressed patients with some viruses, such as Epstein Barr, cytomegalovirus and herpes groups [90], but it is necessary to sequence viral genome for differential diagnosis between viral reactivation or reinfection with a different strain.…”
Section: Discussionmentioning
confidence: 99%
“…Bongiovanni et al examined 677 subjects with at least a positive nasopharyngeal swab, 328 during the first wave and 349 during the second individuating 13 (1.9%) cases of reinfection [25]. Vitale et al examined a cohort of 1579 patients and reported five reinfections (0.31%, 95% CI, 0.03-0.58%), of whom only one was hospitalized and the mean (SD) interval between primary infection and reinfection was longer than 230 (90) days [26].…”
Section: Introductionmentioning
confidence: 99%
“…Seventy-two studies were determined to be of good quality while nine studies were of fair quality (S3 Table). Studies were primarily downgraded for unclear study objectives[63], incomplete case definition[16, 28, 48, 66, 67, 70, 77, 83], non-consecutive subject recruitment[19, 27, 30, 34, 38, 39, 4446, 49, 71, 79, 80, 86, 90], incomparable subjects[79], inadequate length of follow-up[43, 63], inadequate description of statistical methods[39, 46, 80] and inadequate description of results[39, 78]. The most common cause for downgrading studies was non-consecutive recruitment which raised concerns that the included sample could be biased towards a more severe presentation or included more individuals undergoing routine screening.…”
Section: Resultsmentioning
confidence: 99%